DESIGN AND IMPLEMENTATION MULTIPLAYER GAME BASED WEB IN BREW SIMULATOR - PRIHANDITO (NIM 13202151), BOMA
In this final project, writer created a multiplayer online game using PHP programming language. The game will be played from a web browser in BREW simulator. This game is chosen because this genre of game is still rarely made in Indonesia. Most of this games are made abroad. The result of this project is a multiplayer online game that can be played on a web browser in BREW simulator.